Tafsir Al-Qur’an dan Pemahaman tentang Kepemimpinan: Integrasi Nilai-Nilai Islam dalam Konteks Kontemporer - Nurhayati, Nia; Mahmudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine the relationship between Tafsir of the Qur'an and understanding of leadership, with a focus on the integration of Islamic values ​​in the contemporary context. Tafsir of the Qur'an is considered the main source for understanding Islamic teachings, including the concept of leadership reflected in the verses of the Qur'an. A qualitative approach is used to analyze traditional and contemporary interpretations of verses that highlight aspects of leadership.This study discusses the concept of leadership from an Islamic perspective, highlighting the traits and responsibilities of leaders described in the Qur'an. Furthermore, this research proposes the integration of Islamic values ​​into the context of contemporary leadership, emphasizing justice, honesty and social responsibility as the main foundation. Through the development of a leadership model based on the Qur'an, this study contributes to practical and applicable understanding for Muslim leaders in carrying out their role as caliphs on earth Case studies covering the application of Islamic values ​​in specific organizations or institutions provide further understanding of the positive impacts that may arise from the integration of these values. Nevertheless, research also highlights the challenges in implementing Islamic values ​​in the context of contemporary leadership. The results of this research provide in-depth insight into the harmonious relationship between interpretation of the Qur'an and understanding of leadership, as well as providing a basis for developing leadership strategies that are in accordance with Islamic principles. The implications of this research are not only relevant for Muslim leaders, but also for researchers and practitioners interested in incorporating religious values ​​in contemporary leadership contexts. Further research can explore and test Al-Quran-based leadership models in a broader context to expand understanding of their positive influence in creating ethical and effective leadership.